2015
DOI: 10.1002/joc.4352
|View full text |Cite
|
Sign up to set email alerts
|

Trend and interannual variation in summer precipitation in eastern Siberia in recent decades

Abstract: We analysed the long‐term trend and interannual variability in summer (JJA) precipitation over eastern Siberia (90°–140°E, 50°–70°N) for the period 1979–2007. An increasing trend in summer precipitation was observed over large areas (Yenisei and Lena river basins) of eastern Siberia. Summer mean 850‐hPa geopotential height decreased from Siberia to the marginal seas north of Siberia, with the largest decreases occurring over the northern part of eastern Siberia, while increasing trends were found around Mongol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
69
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(82 citation statements)
references
References 31 publications
(54 reference statements)
12
69
1
Order By: Relevance
“…Cold season precipitation was also shown to be declining, primarily in the Aldan River subcatchment [ Rawlins et al ., ]. Given that both spring peak flow and base flow remain relatively stable, the change in MADF can be attributed to a more frequent occurrence of a dipole pattern in atmospheric circulation, driving an increase in summer precipitation over the eastern part of the Lena River basin [ Fujinami et al ., ].…”
Section: Discussionsupporting
confidence: 50%
“…Cold season precipitation was also shown to be declining, primarily in the Aldan River subcatchment [ Rawlins et al ., ]. Given that both spring peak flow and base flow remain relatively stable, the change in MADF can be attributed to a more frequent occurrence of a dipole pattern in atmospheric circulation, driving an increase in summer precipitation over the eastern part of the Lena River basin [ Fujinami et al ., ].…”
Section: Discussionsupporting
confidence: 50%
“…Recently, Fujinami et al (2016) found that the enhanced south-westerly MFC in summer over eastern Siberia was related to changes in stationary Rossby waves along the polar jet across the northern Eurasian continent. They suggested that atmospheric teleconnection was a major factor in the increasing trend and interannual variation in summer precipitation over eastern Siberia, i.e., the Lena basin.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally this east-west dipole pattern is well related to the east-west shift of storm tracks across Siberia (Fukutomi et al 2004(Fukutomi et al , 2007. More recently, Fujinami et al (2016) investigated the spatiotemporal patterns of summer precipitation over eastern Siberia using empirical orthogonal function (EOF) analysis for the period from 1979 to 2007. They showed an increasing trend of summer precipitation for the period (29 years) in eastern Siberia, and also revealed the leading modes of interannual variation in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale atmospheric circulation, which is becoming more erratic under global warming, has a major impact on 3661 precipitation variability (Muñoz-Díaz and Rodrigo, 2006;Fujinami et al, 2016). Change in atmospheric moisture is one of the results of a warming climate.…”
Section: Introductionmentioning
confidence: 99%